Prognostic value and predictive biomarkers of phenotypes of tumour‐associated macrophages in colorectal cancer. (10th January 2022) - Kou, Yu; Li, Zhuoqun; Sun, Qidi; Yang, Shengnan; Wang, Yunshuai; Hu, Chen; Gu, Huijie; Wang, Huangjian; Xu, Hairong; Li, Yan; Han, Baowei
Abstract: Background: The roles of different subtypes of tumour‐associated macrophages (TAMs) in predicting the prognosis of colorectal cancer (CRC) remain controversial. In this study, different subtypes of TAMs were investigated as prognostic and predictive biomarkers for CRC. Methods: Expressions of CD68, CD86 and CD163 were investigated by immunohistochemistry (IHC) and immunofluorescence (IF), and the correlation between the expression of CD86 and CD163 was calculated in colorectal cancer tissues from 64 CRC patients. Results: The results showed that high expressions of CD86 + and CD68 + CD86 + TAMs as well as low expression of CD163 + and CD68 + CD163 + TAMs were significantly associated with favourable overall survival (OS). The level of CD86 protein expression showed a negative correlation with CD163 protein expression. In addition, CD86 protein expression remarkably negatively correlated with tumour differentiation and tumour node metastasis (TNM) stage, while CD163 protein expression significantly positively correlated with tumour differentiation and tumour size. As an independent risk factor, high expression of CD86 TAMs had prominently favourable prognostic efficacy, while high expression of CD68 + CD163 + TAMs had significantly poor prognostic efficacy. Conclusions: These results indicate that CD86 + and CD68 + CD163 + TAMs as prognostic and predictive biomarkers for CRC.